Fast ion conductor composite material and preparation method thereof, secondary battery and electric device
By introducing graphite cores and coated composite layers into the fast-charging negative electrode material, and using the coated composite layer composed of porous oxide, MOF material and lithium salt mixture, the problem of difficult to balance fast charging performance, energy density, first-time efficiency and high-temperature performance in the prior art is solved, and the high energy density, excellent high-temperature performance and first-time efficiency of the battery are achieved.
Patent Information
- Application Number
- CN202510323852.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
While improving the fast charging performance, existing fast charging negative electrode materials have problems such as lower energy density, lower high-temperature performance and lower first efficiency, or when adding fast ion conductor materials, the improvement range is limited, and the first-time efficiency and high-temperature performance have not been improved.
A fast ion conductor composite material is proposed, including a graphite core and a coated composite layer. The coated composite layer consists of porous oxide, MOF material and a mixture of lithium salts. The lithium salt mixture includes lithium aluminum oxide and lithium cobalt oxide, with a molar ratio of (1-5): 1, and the second functional layer consists of amorphous carbon. The material is carbonized by a preparation method to form a conductive network to improve electrochemical properties.
The energy density, high temperature performance and first-time efficiency of the battery are improved, thereby improving the charge and discharge rate performance and power output capability, while also having good flame retardancy and safety performance.
Smart Images

Figure CN119852381A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a fast ion conductor composite material and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] At present, the fast-charging negative electrode materials used in the market are mainly artificial graphite, which mainly improves the fast-charging performance of negative electrode materials by selecting negative electrodes with good isotropy, reducing particle size, secondary granulation and increasing carbon coating. For example, increasing the carbon coating amount will improve the fast-charging performance, but at the same time, the energy density of the material will decrease, the high-temperature performance will decrease, and the first efficiency will decrease. This will cause the fast-charging performance of the negative electrode material to be unable to take into account the energy density, first efficiency, and high-temperature performance at the same time. Alternatively, some fast ion conductor materials can be added to improve the fast-charging performance of the negative electrode material, but the improvement is limited, and there is a problem that the first efficiency and high-temperature performance of the material have not been improved. Summary of the invention
[0003] The main purpose of this application is to propose a fast ion conductor composite material and its preparation method, a secondary battery and an electrical device, aiming to improve the battery's charge and discharge rate performance and power output capacity by improving energy density, high temperature performance and initial efficiency, and having good flame retardancy while taking into account the battery's safety performance.
[0004] To achieve the above object, the present invention provides a fast ion conductor composite material, comprising: a core, the material of the core comprising graphite; and, A coating composite layer at least partially coats the inner core, the coating composite layer comprising a first functional layer and a second functional layer extending outward from the inner core surface in sequence, wherein the material of the first functional layer comprises a porous oxide, an MOF material and a lithium salt mixture, the material of the second functional layer comprises amorphous carbon, the lithium salt mixture comprises at least two lithium salts, the at least two lithium salts comprise lithium aluminum oxide and lithium cobalt oxide, and the molar ratio of the lithium aluminum oxide to the lithium cobalt oxide is (1-5):1.
[0005] In one embodiment, the porous oxide comprises porous alumina; and / or, The porous oxide comprises porous alumina: the specific surface area of the porous alumina is 10-100 m 2 / g, and / or, the porosity of the porous alumina is 50-80%; and / or, The lithium salt mixture comprises lithium aluminum oxide and lithium cobalt oxide; and / or, The MOF material includes at least one of ZnO@Mg-MOF, Zn-MOF808, MOF-74(Zn), MOF-818 and ZIF-8.
[0006] In one embodiment, in the fast ion conductor composite material, the mass ratio of the graphite, the porous oxide and the lithium salt mixture is 100:(1-10):(1-10).
[0007] In one embodiment, the thickness of the first functional layer is 10 nm to 500 nm; and / or, The thickness of the second functional layer is 100nm-500nm.
[0008] The present invention also provides a method for preparing the fast ion conductor composite material, comprising the following steps: S10, mixing a metal chloride, a first dispersant, an alkali solution, a MOF material and graphite to obtain a mixed liquid, performing a first heat treatment on the mixed liquid, and drying to obtain a precursor material; S20, mixing the precursor material of step S10 with a solvent, a lithium supplement agent, a second dispersant and an initiator, performing a second heat treatment and carbonization to obtain an ion conductor composite material.
[0009] In one embodiment, in step S10: The mass ratio of the metal chloride, the first dispersant, the alkali solution, the MOF material and the graphite is (10-100): (1-10): (500-1000): (5-15): 1000; and / or, The metal chloride comprises aluminum chloride; and / or, the mass concentration of the alkali solution in the mixture is 1-2wt%; and / or, The first dispersant comprises at least one of glycerol, polyvinyl pyrrolidone and polyethylene glycol; and / or, The alkali solution includes at least one of ammonia water, sodium hydroxide, potassium hydroxide and calcium hydroxide; and / or, The first heat treatment step includes: heating the reaction at 50-100° C. for 1-3 hours.
[0010] In one embodiment, in step S20: The solvent is ethylene glycol, and the mass ratio of the precursor material, the ethylene glycol, the lithium supplement agent, the second dispersant and the initiator is 100: (10-30): (5-10): (1-3): (1-5); and / or, The lithium supplement comprises Li 5 FeO 4 , Li 6 CoO4 and Li 2 NiO 2 At least one of; and / or, The second dispersant comprises at least one of polyoxyethylene alkylphenol ether, stearyl trimethyl ammonium chloride, triethylhexyl phosphoric acid and methyl amyl alcohol; and / or, The initiator comprises at least one of diacyl peroxide, peroxyester, peroxydicarbonate, peroxyketal and monoperoxycarbonate; and / or, The second heat treatment step comprises heating the reaction at 50-100° C. for 1-3 hours; and / or, The carbonization step includes: sintering at 800-1200° C. for 1-6 hours.
[0011] The present invention also provides a battery, comprising the fast ion conductor composite material as described in any one of the above.
[0012] The present invention also provides an electrical device, comprising the battery as described above.
[0013] The present invention provides a fast ion conductor composite material, comprising a core and a coating composite layer, wherein the coating composite layer at least partially coats the core, wherein the material of the core comprises graphite, which has high conductivity and provides an electron conduction path as the core, and the coating composite layer can avoid contact between graphite and electrolyte to reduce side reactions; the porous oxide and MOF material in the first functional layer have a higher specific surface area and a higher porosity, providing more active sites for the migration and storage of lithium ions; and the lithium salt mixture contains at least two lithium salts, which can provide a fast ion transmission path and be embedded in the pores of the porous oxide and MOF material. It can improve the electrochemical performance of the graphite negative electrode, increase its charge and discharge efficiency, and reduce irreversible capacity loss. At the same time, it can also serve as a lithium ion transmission channel to promote the rapid and uniform embedding / ejection of lithium ions into / from the graphite interlayer, ensuring good electronic conductivity. The second functional layer includes amorphous carbon, which covers the first functional layer to form a conductive network, further improving the electrochemical performance of the fast ion conductor composite material. The fast ion conductor composite material of the present invention improves the energy density, high temperature performance and initial efficiency, thereby improving the charge and discharge rate performance of the battery, enhancing its power output capacity, having good flame retardancy, and taking into account the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0015] Figure 1 This is a scanning electron microscope image (SEM) of the fast ion conductor composite material in Example 4 provided by the present invention.
[0016] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0017] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.
[0018] At present, the fast-charging negative electrode materials used in the market are mainly artificial graphite, which mainly improves the fast-charging performance of the material by selecting a negative electrode with good isotropy, reducing the particle size, secondary granulation and increasing the carbon coating amount. For example, increasing the carbon coating amount will improve the fast-charging performance while reducing the energy density of the material, decreasing the high-temperature performance and reducing its first efficiency. This will cause the fast-charging performance of the negative electrode material to be unable to take into account the energy density, first efficiency and high-temperature performance at the same time. Or add some fast ion conductor materials to improve the fast-charging performance of the material, but the improvement is limited, and there is a problem that the first efficiency and high-temperature performance of the material have not been improved.
[0019] In view of this, in order to achieve the above-mentioned purpose, the present invention proposes a fast ion conductor composite material, comprising a core and a coating composite layer, wherein the core material comprises graphite; and the coating composite layer comprises a first functional layer and a second functional layer extending outward from the surface of the core in sequence, wherein the material of the first functional layer comprises a porous oxide, an MOF material and a lithium salt mixture, the material of the second functional layer comprises amorphous carbon, the lithium salt mixture comprises at least two lithium salts, the at least two lithium salts comprise lithium aluminum oxide and lithium cobalt oxide, the molar ratio of the lithium aluminum oxide to the lithium cobalt oxide is (1-5):1, and the lithium salt mixture comprises lithium aluminum oxide and lithium cobalt oxide, the molar ratio of the lithium aluminum oxide to the lithium cobalt oxide is (1-5):1.
[0020] The present invention proposes a fast ion conductor composite material, comprising a core and a coating composite layer that at least partially coats the core, wherein graphite has high conductivity and serves as a core to provide an electron conduction path, and the coating composite layer can avoid contact between graphite and electrolyte to reduce side reactions; the porous oxide and MOF material in the first functional layer have a higher specific surface area and a higher porosity, providing more active sites for the migration and storage of lithium ions; and the lithium salt mixture contains at least two lithium salts, which can provide a fast ion transmission path and be embedded in the pores of the porous oxide and MOF material, thereby improving the electrochemical properties of the graphite negative electrode, improving its charge and discharge efficiency, and reducing irreversible capacity loss. At the same time, it can also serve as a lithium ion transmission channel to promote the rapid and uniform embedding / ejection of lithium ions into / from graphite layers, thereby ensuring good electron conduction capability; the second functional layer comprises amorphous carbon, which coats the first functional layer to form The conductive network further improves the electrochemical properties of the fast ion conductor composite material. The fast ion conductor composite material of the present invention improves the energy density, high temperature performance and initial efficiency, thereby improving the charge and discharge rate performance of the battery, enhancing its power output capacity, having good flame retardancy, and taking into account the safety performance of the battery. Within this molar ratio range, the two can interact with each other, while improving the rate performance of the material, the structural stability of the material and its safety performance can also be improved. Furthermore, the lithium salt mixture includes lithium aluminum oxide and lithium cobalt oxide, and the molar ratio of the lithium aluminum oxide to the lithium cobalt oxide is (1-5): 1. If the content of lithium cobalt oxide is too little, then the lithium cobalt oxide as the main source of lithium ions means that the number of lithium ions is reduced, which will lead to a decrease in battery capacity. At the same time, it will also lead to the construction of diffusion channels for lithium ions in the material, which will also reduce the rate performance of the battery.
[0021] In some embodiments of the present invention, the porous oxide comprises porous alumina, the porous oxide comprises porous alumina, and the specific surface area of the porous alumina is 10-100 m 2 / g and 50~80% porosity, porous alumina has a large specific surface area and high porosity, which can provide more active sites and electrolyte penetration channels, thereby improving ionic conductivity and still having good discharge capacity and capacity retention rate under high-speed current.
[0022] In some embodiments of the present invention, the lithium salt mixture includes lithium aluminum oxide and lithium cobalt oxide. The use of the above lithium salt mixture can improve the initial efficiency of the material and the transmission rate of lithium ions during the charging and discharging process.
[0023] In some embodiments of the present invention, the MOF material includes at least one of ZnO@Mg-MOF, Zn-MOF808, MOF-74(Zn), MOF-818 and ZIF-8.
[0024] It can be understood that the MOF material is a metal organic framework, which is a porous crystalline material formed by self-assembly of metal ions or clusters and organic ligands, which can enhance the material's liquid absorption capacity and reduce expansion, thereby improving the cycle performance.
[0025] In some embodiments of the present invention, the MOF material includes at least one of ZnO@Mg-MOF, Zn-MOF808, MOF-74(Zn), MOF-818 and ZIF-8, that is, the MOF material can be any one of ZnO@Mg-MOF, Zn-MOF808, MOF-74(Zn), MOF-818 and ZIF-8, or can contain two or more of ZnO@Mg-MOF, Zn-MOF808, MOF-74(Zn), MOF-818 and ZIF-8 at the same time, all of which belong to the protection scope of the present invention. By selecting the above MOF materials, skeleton support and porous structure can be provided to provide more attachment points and reduce expansion and cycle performance.
[0026] In some embodiments of the present invention, in the fast ion conductor composite material, the mass ratio of the graphite, the porous oxide and the lithium salt mixture is 100:(1-10):(1-10). Within the above range, the electrochemical performance of the battery can be optimized.
[0027] In some embodiments of the present invention, the thickness of the first functional layer is 100 nm to 500 nm. A suitable thickness can improve the mechanical strength of the electrode and also improve the interface stability of the electrode.
[0028] In some embodiments of the present invention, the second functional layer has a thickness of 100 nm to 500 nm and mainly acts as a diaphragm to protect the active material and prevent the active material from undergoing side reactions during the cycle, thereby improving the cycle stability of the battery.
[0029] The present invention also provides a method for preparing the fast ion conductor composite material, characterized in that it comprises the following steps: S10, mixing a metal chloride, a first dispersant, an alkali solution, a MOF material and graphite to obtain a mixed liquid, performing a first heat treatment on the mixed liquid, and drying to obtain a precursor material; S20, mixing the precursor material of step S10 with a solvent, a lithium supplement agent, a second dispersant and an initiator, performing a second heat treatment and carbonization to obtain an ion conductor composite material.
[0030] In the technical solution of the present invention, in step S10: first, graphite has a high specific surface area and good electrical conductivity, while the MOF material has a porous structure and an ordered skeleton, which provides a high-speed channel for ion transmission. The metal chloride, the first dispersant, the alkali solution, the MOF material and the graphite are mixed. The dispersant will make the metal chloride and the alkali solution evenly dispersed on the surface of the graphite and the MOF material. The excess metal chloride reacts with the alkali solution to generate metal hydroxide or metal oxide, and through the first heat treatment, part of the metal hydroxide will be further dehydrated to form a porous metal oxide, specifically, it can be porous alumina, so that the metal oxide generated by the reaction is coated on the surface of the graphite and the MOF material to form a first functional layer to improve the safety performance. The first functional layer improves the ionic conductivity and mobility of the fast ion conductor composite material, and at the same time inhibits the growth of crystal dendrites, so that after further using the above-mentioned fast ion conductor composite material to prepare a battery, the safety and cycle life of the battery can be improved.
[0031] In step S20: the solvent is ethylene glycol, which can participate in the reaction as a reducing agent and a reaction medium under the heat treatment conditions, and can also generate intermediate products such as ethylene glycol ether, and release gas, further improving the pore structure of the material. Under the second heat treatment conditions, a part of the lithium supplement will undergo thermal decomposition to generate a second lithium salt mixture and release lithium ions, so that the remaining metal chloride reacts with part of the lithium ions under alkaline conditions to obtain a lithium salt mixture, thereby improving the initial efficiency of the material. The two lithium salt mixtures obtained are attached to the surface of the first functional layer, and the released lithium ions increase the number of lithium ions during the charge and discharge process, thereby improving the rate performance. The other part Under the action of the initiator, the lithium replenisher chemically reacts with the hydroxyl group (-OH) or other active sites on the surface of ethylene glycol to form covalent bonds or other types of strong interactions to form a lithium-containing polymer, which helps to firmly attach the newly generated polymer to the first functional layer to form a coating layer with high ion conductivity and stable structure. At the same time, the cross-linking between the polymer chains will also increase the mechanical strength and stability of the entire system, making the coating layer less likely to fall off. After subsequent carbonization, amorphous carbon is formed, that is, the second functional layer is formed to cover the first functional layer to form a conductive network, which further improves the electrochemical properties of the fast ion conductor composite material.
[0032] In some embodiments of the present invention, in step S10, the mass ratio of the metal chloride, the first dispersant, the alkali solution, the MOF material and the graphite is (10-100): (1-10): (500-1000): (5-15): 1000. In the above range, an excess of metal chloride participates in the reaction, and a part of the metal chloride generates metal oxide after the reaction and is coated on the surface of the graphite and the MOF material to improve the conductivity. Another part of the metal chloride participates in the next round of reaction to generate a lithium salt mixture.
[0033] In some embodiments of the present invention, the metal chloride includes aluminum chloride. The metal chloride of the present invention is preferably aluminum chloride. The mass concentration of the alkali solution in the mixture is 1-2wt%, preferably 1wt%, which helps to ensure that all substances participating in the reaction can be evenly dispersed in the solution, thereby ensuring that the subsequently formed MOF material or other compounds have good crystallinity and repeatability.
[0034] In some embodiments of the present invention, the first dispersant includes at least one of glycerol, polyvinyl pyrrolidone and polyethylene glycol, that is, the first dispersant can be any one of glycerol, polyvinyl pyrrolidone and polyethylene glycol, or two or three of glycerol, polyvinyl pyrrolidone and polyethylene glycol, all of which fall within the scope of protection. The above-mentioned first dispersant can be used to disperse the mixed solution so that the metal oxide is evenly dispersed on the surface of graphite and MOF materials.
[0035] In some embodiments of the present invention, the alkali solution includes at least one of ammonia water, sodium hydroxide, potassium hydroxide and calcium hydroxide. The above alkali solution is mainly used to provide hydroxide ions to generate metal oxides, thereby improving the conductivity of the battery.
[0036] In some embodiments of the present invention, the first heat treatment step includes: heating the reaction at 50-100° C. for 1-3 hours. Within the above heat treatment range, residual solvent and moisture can be removed and the structure of the precursor material can be further stabilized.
[0037] In some embodiments of the present invention, in step S20: The solvent is ethylene glycol, and the mass ratio of the precursor material, the ethylene glycol, the lithium supplement agent, the second dispersant and the initiator is 100: (10-30): (5-10): (1-3): (1-5); within the above range, the precursor material and the lithium supplement agent are mixed, wherein, for example, the precursor material contains aluminum chloride, i.e., ALCl 3 +2OH - +Li + →LiAlO 2 +HCl, while Li 6 CoO 4 →Li + +LiCoO 2 +O 2 , thus obtaining a mixture of two lithium salts, a composite of these two substances, lithium aluminum oxide (LiAlO 2 ) has improved the high energy density and conductivity, while lithium cobalt oxide (LiCoO 2 ) enhances the structural stability and thermal stability. Combining the two can achieve synergistic performance. As the main lithium ion conductor, it provides an efficient ion migration path and improves the electrochemical performance.
[0038] Furthermore, during the use of ethylene glycol, ethylene glycol needs to be added to N-methylpyrrolidone (NMP) to prepare a 1wt% solution, which can improve solubility, reduce viscosity, improve electrochemical performance, promote dispersion and control reaction conditions.
[0039] In some embodiments of the present invention, the lithium supplement comprises Li 5 FeO 4 , Li 6 CoO 4 and Li 2 NiO 2 At least one of them is mainly used to supplement lithium ions, increase the number of lithium ions, improve rate performance, and also generate a lithium salt mixture to further improve conductivity.
[0040] In some embodiments of the present invention, the second dispersant includes at least one of polyoxyethylene alkylphenol ether, stearyl trimethyl ammonium chloride, triethylhexyl phosphate and methyl amyl alcohol, and is mainly used to disperse the mixed solution, which helps to uniformly distribute the raw materials and improve the preparation efficiency.
[0041] In some embodiments of the present invention, the initiator includes at least one of diacyl peroxide, benzoyl peroxide, peroxyester, peroxydicarbonate, peroxyketal and monoperoxycarbonate. Any of the above initiators is used to start the polymerization reaction to form a polymer. Subsequent carbonization can form amorphous carbon, which can inhibit the decomposition of the functional layer in a high temperature environment and extend the cycle life.
[0042] In some embodiments of the present invention, the second heat treatment step includes heating the reaction at 50-100°C for 1-3 hours. Within the above range, it can not only promote the complete chemical reaction, but also maintain an appropriate sintering temperature to enable the material to form an ideal crystal structure, which is beneficial to the rapid conduction of ions.
[0043] The carbonization step includes: sintering at 800-1200°C for 1-6 hours. Within the above range, a stable carbon structure can be formed, electrical conductivity can be improved, pore structure can be optimized, heat resistance and chemical stability can be enhanced, impurity content can be reduced, and the morphology of the material can be controlled.
[0044] The present invention also provides a secondary battery, comprising the fast ion conductor composite material as described in any one of the above.
[0045] The present invention further provides an electrical device, including the battery as described above. For example, the electrical device proposed in this application includes but is not limited to: a mobile phone, a portable device or a laptop computer, etc.
[0046] The above-mentioned battery and electrical device both contain the fast ion conductor composite material of the present invention, and thus have all the above-mentioned beneficial effects, which will not be described one by one here.
[0047] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0048] Example 1 A fast ion conductor composite material comprises a core and a functional layer coated on the core; The core comprises graphite, the functional layers are provided with a plurality of layers, the coating composite layer comprises a first functional layer and a second functional layer extending outward from the surface of the core in sequence, the material of the first functional layer comprises porous alumina, and the material of the second functional layer comprises a lithium salt mixture, namely, lithium aluminum oxide and lithium cobalt oxide; wherein the molar ratio of the lithium aluminum oxide to the lithium cobalt oxide is 4:1; The specific surface area of the porous alumina is 50 m 2 / g; the mass ratio of the graphite to the porous alumina is 100:5; the mass ratio of the graphite to the lithium salt mixture is 100:5; the thickness of the first functional layer is 300nm; the thickness of the second functional layer is 300nm.
[0049] Example 2 Example 2 is similar to Example 1, except that: The molar ratio of the lithium aluminum oxide to the lithium cobalt oxide is 1:1; The specific surface area of the porous alumina is 10 m 2 / g; the mass ratio of the graphite to the porous alumina is 100:1; the mass ratio of the graphite to the lithium salt mixture is 100:1; the thickness of the first functional layer is 100nm; the thickness of the second functional layer is 100nm.
[0050] Example 3 Example 3 is similar to Example 1, except that: The molar ratio of the lithium aluminum oxide to the lithium cobalt oxide is 5:1; The specific surface area of the porous alumina is 100 m 2 / g; the mass ratio of the graphite to the porous alumina is 10:1; the mass ratio of the graphite to the lithium salt mixture is 10:1; the thickness of the first functional layer is 500nm; the thickness of the second functional layer is 500nm.
[0051] Example 4 A method for preparing a fast ion conductor coated graphite composite material comprises the following steps: Step S10: 100 g of aluminum chloride, 5 g of glycerol, 800 g of an ammonia solution with a mass concentration of 1 wt%, and 10 g of ZnO@Mg-MOF were configured into a mixed solution, and then 1000 g of artificial graphite was added to the mixed solution, and a chemical reaction was carried out at a temperature of 80 ° C for 2 h, filtered, and vacuum dried at 80 ° C for 24 h to obtain a precursor material; Step S20: 20 g of polyvinyl alcohol was added to 2000 g of N-methylpyrrolidone to prepare a 1 wt% solution, and then 8 g of Li 5 FeO 4, 2g of polyoxyethylene alkylphenol ether is evenly dispersed, 100g of precursor material is added and mixed evenly, and 3g of diacyl peroxide is added and reacted at a temperature of 80°C for 2h, filtered, and the filter residue is sintered at a high temperature of 1000°C for 3h to obtain a fast ion conductor composite material, wherein the molar ratio of the lithium aluminum oxide to the lithium cobalt oxide is 3.5:1.
[0052] Example 5 A method for preparing a fast ion conductor coated graphite composite material comprises the following steps: Step S10: 100g zirconium tetrachloride, 1g polyvinyl pyrrolidone, 500g sodium hydroxide solution with a mass concentration of 1wt%, and 5g Zn-MOF808 are configured into a mixed solution, and then 1000g artificial graphite is added, and a chemical reaction is carried out at a temperature of 50°C for 3h, filtered, and the obtained filter residue is vacuum dried at 80°C for 24h to obtain a precursor material; Step S20: Add 10g of polyvinyl alcohol to 1000g of N-methylpyrrolidone to prepare a 1wt% solution, then add 5g of Li6CoO4 and 1g of stearyltrimethylammonium chloride and disperse them evenly, then add 100g of the precursor material and mix them evenly, and add 1g of peroxide ester to react at a temperature of 50°C for 3h, filter, and sinter the resulting filter residue at a high temperature of 800°C for 6h to obtain a fast ion conductor composite material.
[0053] Example 6 A method for preparing a fast ion conductor coated graphite composite material comprises the following steps: Step S10: 100 g of niobium chloride, 10 g of polyethylene glycol, 1000 g of a 1 wt% potassium hydroxide solution, and 15 hMOF-74 (Zn) were prepared into a mixed solution, and then 1000 g of artificial graphite was added, and a chemical reaction was carried out at a temperature of 100 ° C for 1 h, and the obtained filter residue was vacuum dried at 80 ° C for 24 h to obtain a precursor material; Step S20: 30 g of polyvinyl alcohol was added to 3000 g of N-methylpyrrolidone to prepare a 1 wt% solution, and then 10 g of Li 2 NiO 2 , 3g of methyl pentanol was evenly dispersed, then 100g of the precursor material was added and mixed evenly, and 5g of peroxydicarbonate was added and reacted at a temperature of 100°C for 1h. After filtering, the filter residue was sintered at a high temperature of 1200°C for 1h to obtain a fast ion conductor composite material.
[0054] Comparative Example 1 Comparative Example 1 is different from Example 4 in that no lithium supplement (Li 5 FeO 4 ) and a second dispersant (polyoxyethylene alkylphenol ether), and the rest are the same as in Example 4.
[0055] Comparative Example 2 The difference between Comparative Example 2 and Example 4 is that ZnO@Mg-MOF is not added, and the rest is the same as Example 4.
[0056] Comparative Example 3 The difference between Comparative Example 3 and Example 4 is that the mass ratio of the graphite to the metal oxide is 100:0.5, that is, 5 g of aluminum chloride is added, that is, only one lithium salt (lithium cobalt oxide), and the rest is the same as Example 4.
[0057] Comparative Example 4 Comparative Example 4 is different from Example 4 in that aluminum chloride is not added, that is, porous oxide is not formed, and the rest is the same as Example 4.
[0058] Comparative Example 5 The difference between Comparative Example 5 and Example 4 is that the molar ratio of the lithium aluminum oxide to the lithium cobalt oxide in Comparative Example 5 is 0.5:1, and the rest is the same as Example 4.
[0059] Performance Testing (1) SEM test The fast ion conductor coated graphite composite material prepared in Example 4 was subjected to SEM test, and the results are as follows: Figure 1 As shown. Figure 1 It can be seen that the obtained composite material presents a secondary granular structure with slight bonding phenomenon, the particle size is between 10-15 μm, and the size distribution is uniform.
[0060] (2) Button battery test The fast ion conductor composite materials prepared in Examples 4-6 and the fast ion conductor composite materials in Comparative Examples 1-5 were assembled into button batteries according to the following method: Add a binder, a conductive agent, and a solvent to the fast ion conductor composite material, stir and mix them evenly to form a negative electrode slurry, apply the negative electrode slurry on a copper foil, dry, roll, and cut to obtain a negative electrode sheet. The binder is polyvinylidene fluoride, the conductive agent is SP conductive agent, and the solvent is NMP. The weight ratio of the negative electrode material, SP conductive agent, polyvinylidene fluoride and NMP is 95:1:4:220. The metal lithium sheet is used as the counter electrode, the polyethylene (PE) film is used as the diaphragm, and the LiPF 6 / EC+DEC(LiPF 6 The concentration of EC was 1.3 mol / L, the volume ratio of EC and DEC was 1:1) as the electrolyte, and the battery was assembled in an argon-filled glove box.
[0061] The button cells were installed on the Wuhan Blue Power CT2001A battery tester, and charged and discharged at a rate of 0.1C, with a charge and discharge voltage range of 0.005V-2.0V, and the first discharge capacity and first discharge efficiency were measured. The battery's charge DCR (50% SOC) and cycle performance (0.1C / 0.1C, 100 weeks) were also tested.
[0062] According to the national standard GB / T-24533-2019 "Graphite Anode Materials for Lithium-ion Batteries", the first discharge specific capacity, first charge and discharge efficiency, tap density, specific surface area, powder conductivity, powder OI value, DCR and cycle performance of the above-mentioned fast ion conductor composite materials were tested. The test results are shown in Table 1: Table 1
[0063] It can be seen from Table 1 that the discharge specific capacity and DCR of the fast ion conductor composite materials prepared in Examples 4-6 are significantly better than those in Comparative Examples 1-5; this is because the porous metal alumina fast ion conductor coated with lithium on the surface of the graphite material reduces its irreversible capacity and increases the transmission rate of lithium ions, thereby improving the electronic and ionic conductivity of the material and its initial efficiency; at the same time, a mixture of lithium aluminate / lithium cobaltate or lithium iron phosphate is coated on the surface of the material to restrain the expansion of the inner core graphite and utilize the low expansion rate of the MOF itself to improve the cycle performance.
[0064] Compared with Example 4, in Comparative Example 2, during the preparation of the battery, due to the lack of skeleton support of MOFs, there are also fewer porous structures. The pores in MOFs can not only provide adsorption, but also serve as catalyst active centers. When these structures are missing, the liquid retention performance of the material is reduced, and the cycle performance and ion transfer rate are reduced, and the rate performance is reduced. At the same time, the lack of MOF material causes the expansion of the material to increase, reducing the cycle performance.
[0065] (3) Soft pack battery test The fast ion conductor composite materials prepared in Examples 4-6 and Comparative Examples 1-5 were used to prepare the negative electrode, lithium iron phosphate was used as the positive electrode material to prepare the positive electrode, and LiPF 6 (the solvent is EC+DEC, the volume ratio is 1:1, the concentration is 1.1mol / L) as the electrolyte and celegard2400 as the separator to prepare a 2Ah soft-pack battery.
[0066] When preparing the negative electrode, a binder, a conductive agent, and a solvent are added to the negative electrode material, stirred and mixed to form a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, dried, rolled, and cut to form a negative electrode sheet. The binder is LA132 binder, the conductive agent is SP conductive agent, the solvent is double distilled water, and the weight ratio of the negative electrode material, SP conductive agent, LA132 binder and double distilled water is 95:1:4:220.
[0067] 1) Rate performance test The charge and discharge voltage range is 2.5~3.65V, the test temperature is 25±3.0℃, and the charging is performed at 1.0C, 2.0C, 3.0C, and 5.0C, and the discharge is performed at 1.0C. The constant current ratio of the battery under different charging modes is tested, and the results are shown in Table 2: Table 2
[0068] It can be seen from Table 2 that the rate charging performance of the battery pack of the present invention is significantly better than that of the comparative example, and the charging time is shorter. This is because the example material has excellent powder conductivity and its low OI value improves the fast charging performance of the material.
[0069] Compared with Comparative Example 1, the lithium supplement (Li 5 FeO 4 ) and a second dispersant, so that the lithium supplement agent is evenly attached to the surface of the first functional layer with the two lithium salt mixture, and an organic lithium salt layer can be obtained, that is, a second functional layer is formed, which is superimposed on the surface of the first functional layer, greatly improving the conductivity. Therefore, the fast ion conductor composite material prepared in the embodiment has high powder conductivity and improves the constant current ratio of the material.
[0070] Compared with Comparative Example 2, since the comparative example lacks the skeleton support of MOFs and has less porous structure, the liquid retention performance of the material is reduced, causing the transmission rate of lithium ions during its charge and discharge process to slow down, thereby greatly reducing the rate performance.
[0071] Compared with Comparative Example 3, due to less aluminum chloride, lithium aluminate compound cannot be formed, which reduces the insertion and extraction rate of lithium ions during charging and discharging, and reduces its rate performance.
[0072] Compared with Comparative Example 4, there is no porous structure, the specific surface area is reduced, the diffusion coefficient of the material is reduced, and the rate performance is reduced.
[0073] Compared with Comparative Example 5, due to the higher content of lithium cobalt oxide, that is, the material contains more lithium supplement, more lithium cobalt oxide is formed by decomposition, and fewer lithium ions react with aluminum chloride to form lithium aluminum oxide, and another part of lithium reacts with amorphous carbon to form dead lithium, which limits the improvement of the diffusion rate of lithium ions in the material, but reduces the diffusion rate of charging and discharging lithium ions, thereby reducing its rate performance.
[0074] 2) Cycle performance test The soft-pack batteries made of the fast ion conductor composite materials in Examples 4-6 and Comparative Examples 1-5 were subjected to the following experiment: 100 and 500 charge and discharge cycles were performed at a 2C / 2C charge and discharge rate and a voltage range of 2.5-3.65V, respectively, to test their capacity retention rate. The results are shown in Table 3: Table 3
[0075] It can be seen from Table 3 that the cycle performance of the lithium ion battery prepared with the fast ion conductor composite material prepared in the present invention is better than that of the comparative example. The reason is that the fast ion conductor composite material coated on the graphite surface improves the structural stability of the material and the coated MOF material reduces expansion and improves the cycle performance.
[0076] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A fast ion conductor composite material, characterized in that: include: a core, the material of the core comprising graphite; and, A coating composite layer at least partially coats the inner core, the coating composite layer comprising a first functional layer and a second functional layer extending outward from the inner core surface in sequence, wherein the material of the first functional layer comprises a porous oxide, an MOF material and a lithium salt mixture, the material of the second functional layer comprises amorphous carbon, the lithium salt mixture comprises at least two lithium salts, the at least two lithium salts comprise lithium aluminum oxide and lithium cobalt oxide, and the molar ratio of the lithium aluminum oxide to the lithium cobalt oxide is (1-5):
1.
2. The fast ion conductor composite material according to claim 1, characterized in that: The porous oxide comprises porous alumina; and / or, The porous oxide comprises porous alumina: the specific surface area of the porous alumina is 10-100 m 2 / g, and / or, the porosity of the porous alumina is 50-80%; and / or, The MOF material includes at least one of ZnO@Mg-MOF, Zn-MOF808, MOF-74 (Zn), MOF-818 and ZIF-8.
3. The fast ion conductor composite material according to claim 1, characterized in that: In the fast ion conductor composite material, the mass ratio of the graphite, the porous oxide and the lithium salt mixture is 100:(1-10):(1-10).
4. The fast ion conductor composite material according to claim 1, characterized in that: The thickness of the first functional layer is 10 nm to 500 nm; and / or, The thickness of the second functional layer is 100nm-500nm.
5. A method for preparing a fast ion conductor composite material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S10, mixing a metal chloride, a first dispersant, an alkali solution, a MOF material and graphite to obtain a mixed liquid, performing a first heat treatment on the mixed liquid, and drying to obtain a precursor material; S20, mixing the precursor material of step S10 with a solvent, a lithium supplement agent, a second dispersant and an initiator, performing a second heat treatment and carbonization to obtain an ion conductor composite material.
6. The method for preparing the fast ion conductor composite material according to claim 5, characterized in that: In step S10: The mass ratio of the metal chloride, the first dispersant, the alkali solution, the MOF material and the graphite is (10-100): (1-10): (500-1000): (5-15): 1000; and / or, The metal chloride comprises aluminum chloride; and / or, The mass concentration of the alkali solution in the mixture is 1-2wt%; and / or, The first dispersant comprises at least one of glycerol, polyvinyl pyrrolidone and polyethylene glycol; and / or, The alkali solution includes at least one of ammonia water, sodium hydroxide, potassium hydroxide and calcium hydroxide; and / or, The first heat treatment step includes: heating the reaction at 50-100° C. for 1-3 hours.
7. The method for preparing the fast ion conductor composite material according to claim 5, characterized in that: In step S20: The solvent is ethylene glycol, and the mass ratio of the precursor material, the ethylene glycol, the lithium supplement agent, the second dispersant and the initiator is 100: (10-30): (5-10): (1-3): (1-5); and / or, The lithium supplement comprises at least one of Li5FeO4, Li6CoO4 and Li2NiO2; and / or, The second dispersant comprises at least one of polyoxyethylene alkylphenol ether, stearyl trimethyl ammonium chloride, triethylhexyl phosphoric acid and methyl amyl alcohol; and / or, The initiator comprises at least one of diacyl peroxide, benzoyl peroxide, peroxyester, peroxydicarbonate, peroxyketal and monoperoxycarbonate; and / or, The second heat treatment step comprises heating the reaction at 50-100° C. for 1-3 hours; and / or, The carbonization step includes: sintering at 800-1200° C. for 1-6 hours.
8. A secondary battery, characterized in that: The fast ion conductor composite material comprises the fast ion conductor composite material as described in any one of claims 1 to 4 or the fast ion conductor composite material prepared by the preparation method of the fast ion conductor composite material as described in any one of claims 5 to 7.
9. An electrical device, characterized in that: A secondary battery comprising the secondary battery as claimed in claim 8.
Citation Information
Patent Citations
High-specific-capacity composite negative electrode material, preparation method and lithium ion battery
CN111834615A
High-energy-density fast-charging graphite composite negative electrode material, preparation method thereof and lithium ion battery
CN113555539A
Preparation method of solid electrolyte coated graphite composite material
CN113889595A
Graphite negative electrode composite material, preparation method thereof and lithium ion battery
CN115207304A
Preparation method of negative electrode material for long-circulation lithium ion battery
CN115893400A